2016
DOI: 10.1007/s11701-016-0583-y
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after robotic myomectomy: is it associated with use of GnRH agonist?

Abstract: Gonadotropin-releasing hormone (GnRH) agonist therapy is used before myomectomy to decrease the size of the fibroids, but its association with fibroid recurrence postoperatively remains unsettled. We undertook a retrospective study of robotic-assisted myomectomy (RM) patients at our academic medical center to determine symptomatic recurrence and reoperation rates in those who did versus did not receive preoperative GnRH therapy. Only patients, who had their index myomectomy at least 2 years prior to the chart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…No reply was received and these four studies were all excluded for further data extraction and analysis. Finally, 23 studies met our inclusion criteria and were used for data extraction [ 14 – 36 ]. Fourteen of the included studies reported on laparotomic myomectomies, eight studies on laparoscopic myomectomies and one study reported on both laparotomic and laparoscopic myomectomies [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No reply was received and these four studies were all excluded for further data extraction and analysis. Finally, 23 studies met our inclusion criteria and were used for data extraction [ 14 – 36 ]. Fourteen of the included studies reported on laparotomic myomectomies, eight studies on laparoscopic myomectomies and one study reported on both laparotomic and laparoscopic myomectomies [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only the study of Sangha et al [ 36 ] did not report on conversion rate. In all other studies performing laparoscopic myomectomy (n = 430), no conversions to open procedures occurred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of them, age, myoma size, and the number of myomas were suggested as the risk factors for fibroid recurrence (11)(12)(13)(14)(15). Other risk factors, such as preoperative GnRH therapy and postoperative pregnancy, were also pointed out as risk factors for fibroid recurrence in some studies (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that it is likely because of the extraction of small leiomyomas, which is less exhausting in manual removal than in the laparoscopic approach. The growth of residual myoma masses then results in newly diagnosed fibroids, which are considered recurrences [37] . Considering the better flexibility of robotic instruments, enucleation of small myomas should be more accessible, leading to lower recurrence.…”
Section: Fertility and Obstetrical Outcomes And Recurrencementioning
confidence: 99%